2015
DOI: 10.1016/j.adolescence.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Relations between youths' conceptions of spirituality and their developmental outcomes

Abstract: This study uses a positive youth development (PYD) approach to explore whether differences in youths' conceptions of spirituality were linked to patters of difference regarding 6 domains of PYD. Using data from the 4-H Study of Positive Youth Development, findings revealed a consistent trend across 6 domains of positive development. Youth who had coherent conceptions of being spiritual generally scored highest on measures of positive development, whereas youth in the ambiguous spirituality group (i.e., less co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Such a wide spectrum of conceptualizations of spirituality presents challenges in empirical research (Koenig, ; Speed, ). Across those conceptions, empirical reports have found correlations between indicators of PYD and youths’ spirituality (e.g., James & Fine, ; Warren et al., ), bolstering the claims of its significance in PYD. We utilize James and Fine's () tripartite model to conceptualize spirituality that was developed based on adolescents’ own narratives of what it means to be spiritual, a historically neglected perspective (Smith & Denton, ).…”
Section: Conceptualizing Spiritualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Such a wide spectrum of conceptualizations of spirituality presents challenges in empirical research (Koenig, ; Speed, ). Across those conceptions, empirical reports have found correlations between indicators of PYD and youths’ spirituality (e.g., James & Fine, ; Warren et al., ), bolstering the claims of its significance in PYD. We utilize James and Fine's () tripartite model to conceptualize spirituality that was developed based on adolescents’ own narratives of what it means to be spiritual, a historically neglected perspective (Smith & Denton, ).…”
Section: Conceptualizing Spiritualitymentioning
confidence: 99%
“…Across those conceptions, empirical reports have found correlations between indicators of PYD and youths’ spirituality (e.g., James & Fine, ; Warren et al., ), bolstering the claims of its significance in PYD. We utilize James and Fine's () tripartite model to conceptualize spirituality that was developed based on adolescents’ own narratives of what it means to be spiritual, a historically neglected perspective (Smith & Denton, ). Furthermore, RDS models of human development emphasize that the individual is an active agent in their own socialization (Overton & Molenaar, ), thus having a model that allow for youths’ own conceptualizations of spirituality align with the theoretical grounding of this study.…”
Section: Conceptualizing Spiritualitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, many of these studies tend to focus more generally on connections between religiosity and generosity without testing the possible mechanisms for these effects. For instance, James and Fine found that adolescent participants coded as having a more coherent spirituality or sense of purpose (as opposed to an ambiguous spirituality) scored higher on measures of all six "Cs" of positive youth development (i.e., Competence, Confidence, Character, Connection, Caring/Compassion, and Contribution), with higher scores on the Contribution factor indicating higher levels of generosity [9]. Similarly, Spiewak and Sherrod found that generosity was correlated with religious beliefs, spiritual transcendence, and religious practices in a cross-sectional sample of adolescents and emerging adults [10], and Bussing, Kerksieck, Günther, and Baumann found that spirituality and religiousness were correlated with generative altruism in adolescents and emerging adults [11].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, have open dialogue with their adolescent children about their spirituality. This can help them clarify their notions of spirituality, with research has been shown to also be linked to positive development (James and Fine 2015), specifically allowing them to clarify their notions of spirituality. Also, parents can find mentors for their teen children, but mentors that will intentionally invest in the process of helping youth clarify and internalizing spiritual values.…”
Section: Putting Spirituality Into Practicementioning
confidence: 99%